Implementation Of Electronic Government At The Department On Integrated One Door Investment And Licensing Services, Deli Serdang Regency - Muhammad Fairuz Arief (IHSA Institute, 2022)
E-government policy is one form of reform in the implementation of services for the public in Indonesia which aims to improve effectiveness, efficiency, transparency, and accountability in public service implementing institutions in terms of achieving organizational goals. The purpose of this study was to find out how the implementation of Electronic Government at the Department of Investment and One Stop Integrated Licensing Services (DPMPPTSP) Deli Serdang Regency.The method used in this research is descriptive qualitative. This method aims to explain reality contextually, interpret phenomena that are of concern to researchers and understand participants' perspectives on the problems that occur. The types of data used are primary data and secondary data. Primary data was obtained through interviews with resource persons, and secondary data was obtained through literature and documentation studies. The data analysis technique used is a model approach with data reduction, data presentation, and drawing conclusions.The results of this study reveal that E-government in DPMPPTSP can be implemented quite well from increasing the effectiveness and efficiency of licensing services. The communication factors, resources, disposition, and bureaucratic structure in DPMPPTSP are also quite good. The absence of spatial planning regulations makes the licensing process inefficient because it adds to the bureaucracy. DPMPPTSP is advised to provide ICT technical training to employees so that DPMPPTSP's performance is even better.